Metabolites of the phenylpropanoid pathway and physiological quality of soybean seeds in storage - Abati,Julia (2021)
Abstract: The aim of this study was to evaluate changes in the physiological quality of soybean seeds throughout a storage period in two environments, and to evaluate how these changes are related to metabolites of the phenylpropanoid pathway. A completely randomized experimental design was used in a 4 × 8 factorial arrangement (storage periods × cultivars) with four replications. We used seeds from cultivars with contrasts in lignin content, color, and presence of anthocyanin in the seed coat, and isoflavone content in the seed. The seeds were kept for six months under cold and dry storage and in a non-controlled environment. Germination, first germination count, seedling emergence, and tetrazolium testing were performed on the seeds every two months. The physiological quality of the seeds declines during the storage period, with higher rates of decrease in the non-controlled environment. The metabolites of the phenylpropanoid pathway that were studied, especially lignin, affect seed storage potential. Cultivars with higher lignin content show greater storage potential, especially in a non-controlled environment.